2015
DOI: 10.1016/j.buildenv.2015.02.003
|View full text |Cite
|
Sign up to set email alerts
|

The influence of tenure status on housing satisfaction and indoor environmental quality in Finnish apartment buildings

Abstract: Please cite this article as: Pekkonen M, Du L, Skön J-P, Raatikainen M, Haverinen-Shaughnessy U, The influence of tenure status on housing satisfaction and indoor environmental quality in Finnish apartment buildings, Building and Environment (2015), doi: 10.1016/j.buildenv.2015 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…As Turunen et al (2014), Willich et al (2006) and Pekkonen et al (2015) suggest, higher density transportation and public access areas are prone to dust, particulate matter, and gas and noise pollution. These consequently affect the health of the occupants.…”
mentioning
confidence: 99%
“…As Turunen et al (2014), Willich et al (2006) and Pekkonen et al (2015) suggest, higher density transportation and public access areas are prone to dust, particulate matter, and gas and noise pollution. These consequently affect the health of the occupants.…”
mentioning
confidence: 99%
“…The studies conducted by Safian & Nawawi, (2013), Dinarvandi et al, (2014), Agarwal, Patil, &Mehar, (2013), andErbıyık et al, (2012) showed that they have chosen tenants, owners and also property users as respondents in achieving the goal of producing importance of each characteristic of houses. Other research conducted by Ho et al, (2005), Pekkonen, Du, Skon, Raatikainen, & Haverinen-Shaughnessy, (2015, Mulliner, Smallbone, & Maliene, (2013) and Khoiry et al, (2012) has shown that they have preferences to choose users, occupants, and owners of houses in their research as they were the residents of the houses and had the highest information relating towards their properties. Based on the actions from previous researchers, the researcher has concluded that the occupants will the most suitable respondents in the measurement of weightage of importance towards characteristics of houses.…”
Section: Weightage Of Importance For Building Locational and Neighbourhood Characteristics Of Housesmentioning
confidence: 95%
“…The dimensions of interior space are based on the area of the property. Some people prefer to live in a bigger space, while others, especially young people, prefer to live in a smaller place (Pekkonen et al, 2015). If people wishing to live in a bigger place have low incomes, the probability of choosing an estate in the suburbs will increase (Ho et al, 2015).…”
Section: Dimensionsmentioning
confidence: 99%
“…In 2010, the results of a survey in Korea showed that, among various residential properties, 59% of the population has apartments as their main place of residence. In Finland, 80% of people live in apartments (Pekkonen et al, 2015), especially the younger population; however, the poor design of the housing properties cannot meet the needs of different customers (Lee & Ha, 2013). It is moreover interesting to note that, in developed countries, people spend more than 90% of their time indoors (Fasolo, 2016;Frontczak & Wargocki, 2011).…”
mentioning
confidence: 99%